KEADILAN KOMPENSASI DALAM PERSEPSI PEKERJA WANITA HAMIL DAN MELAHIRKAN - Fortunata Susanto, Sanny; Suharti, Lieli; Sirine, Hani (Proceeding SENDI_U, 2015)
Workers is are the most important factors of production within an enterprise to achieve goals and to determinethe progress of a company. The company should establish regulations regarding workers compensationespecially for pregnant and giving birth workers. The company must ensure the safety, security and comfort ofthe workforce. Therefore, the company shall establish regulations that comply with National labor Regulations.The objectives of this research was to find out whether the pregnant female workers are treated fairly regardingtheir compensations in terms of financial and non financial compensations. About 101 femake workers fromplywood industry in Central Java were chosen as respondents of this study. The results of this study showed thatrespondents perceived the implementation of regulation of wages, social security, the availability of leave, andthe protection of health and safety from the company they worked are good enough in accordance with thecompany regulationas and National labor regulations.Keywords: pregnant woman workers, compensation, justice, discrimination